QB 1 - Lupica, Mike (Philomel Books, an imprint of Penguin Group (USA) Inc., 2013)
Jake Cullen, fourteen, lives in the shadows of his father and older brother until he becomes the starting quarterback for the high school football team and finally has his chance to shine.